Interpretation of the formation of physical qualities in a person in scientific and historical sources - Abdumannatov Abdumajid (Zien Journals, 2022)
The article describes the interpretation of the formation of physical qualities in a person in scientific and historical sources and the pedagogical prerequisites for their use in the system of professional development.
Keywords: Person; physical; quality; formation